Tuning the Electrochemical and Photophysical Properties of Osmium-Based Photoredox Catalysts - Goldschmid, Samantha L.; Bednářová, Eva; Beck, Logan R.; Xie, Katherine; Tay, Nicholas E. S.; Ravetz, Benjamin D.; Li, Jun; Joe, Candice L.; Rovis, Tomislav (Synlett, 2022)
The use of low-energy deep-red (DR) and near-infrared (NIR) light to excite chromophores enables catalysis to ensue across barriers such as materials and tissues. Herein, we report the detailed photophysical characterization of a library of OsII polypyridyl photosensitizers that absorb low-energy light. By tuning ligand scaffold and electron density, we access a range of synthetically useful excited state energies and redox potentials.1 Introduction1.1 Scope1.2 Measuring Ground-State Redox Potentials1.3 Measuring Photophysical Properties1.4 Synthesis of Osmium Complexes2 Properties of Osmium Complexes2.1 Redox Potentials of Os(L)2-Type Complexes2.2 Redox Potentials of Os(L)3-Type Complexes2.3 UV/Vis Absorption and Emission Spectroscopy3 Conclusions
Keywords: photoredox catalysis; near-infrared; ligand design